Emerging Trends and Opportunities in the Changing Banking Scenario: A Study of Developing Countries - Surabhi H. Oriya; Varsha Virani (Journal of Social Commerce, 2023)
A developed banking system is now very well established, including many kinds of banks, including public sector banks, foreign banks, both old and new private sector banks, regional rural banks, and cooperative banks with funding from the Reserve Bank of India. The banking sector is expanding at a rate that has never been seen before, and it is becoming more diverse than at any other time in the history of banking. In most developing nations, bank assets make up well over 80% of all financial sector assets, although these percentages are noticeably lower in established markets. More than two-thirds of his banking assets are held by the five largest (often local) banks in the majority of developing nations. The alteration in the nature of the dominant structure in the landscape is of utmost importance. Since the 1980s, banks have grown in size and the range of their operations, with some developing into very large institutions dispersed across the nation. This essay analyzes the changes and advancements in the Indian banking sector.